Effect of rituximab on heart involvement in systemic sclerosis - L. A. Garzanova; L. P. Ananyeva; O. A. Koneva; O. B. Ovsyannikova (Научно-практическая ревматология, 2019)
As of now, there has been a great body of data on the use of rituximab (RTM) in systemic sclerosis (SS), mainly on its positive effect on skin fibrosis and lung injury. However, information is still scarce about the effect of RTM on other organs and systems, namely the heart affected by SS.Objective: to assess the time course of changes in the signs of heart involvement in SS patients one year after initiation of RTM therapy.Subjects and methods. The paper gives data on changes in cardiac disorders in 71 patients with SS one year after the prescription of RTM.Results and discussion. The rate of cardiac rhythm and conduction disorders and diastolic dysfunction was unchanged. At the same time, a significant increase in left ventricular ejection fraction (EF) and a reduction in the severity of dyspnea was achieved, which correlated with improved lung function (a significant rise in forced vital capacity). The results of treatment in three patients with predominant heart involvement associated with SS (coronary heart disease and hypertension were ruled out) were considered in detail. These patients displayed pronounced positive changes as increased EF, less severe cardiac arrhythmias, reduced chronic heart failure, better quality of life, as well as the synchronicity of lower disease activity, less skin induction, improved lung function, and stabilized pulmonary artery systolic pressure.Conclusion. RTM in combination with traditional therapy can be considered as a potentially effective drug for the treatment of heart involvement in SS.